The case for people's quantitative easing - Coppola, Frances (Cambridge, U.K. : Polity Press, 2019)
"As the 2008 financial crisis ravaged economies, central banks feared a return to the 1930s. To prevent this, they created trillions of dollars of new money, and poured it into financial markets. Quantitative Easing (QE) was supposed to prevent deflation and restore economic growth. But the money didnt go to the people who had lost their jobs and their homes. It went to the rich, who didnt need it. It went to big corporations, who used it to buy back their own shares and pay their executives big salaries. And it went to banks the same banks whose reckless lending had nearly broken the economy. There wasnt a repeat of the Great Depression, but there certainly wasnt a recovery. Instead, there was a decade of stagnation. Its clear: QE failed. In this book, Frances Coppola makes the case for a different type of QE. Instead of buying assets, central banks should give money directly to ordinary people and small businesses. QE for the People is the fairest and most effective way of restoring crisis-hit economies and helping to solve the long-term challenges of ageing populations, automation and climate change"--
"As the 2008 financial crisis ravaged economies, central banks turned to quantitative easing to prevent a return to the 1930s. There wasn't a repeat of the Great Depression, but there certainly wasn't a recovery. Instead, there was a decade of stagnation. It's clear: QE failed. In this book, Frances Coppola makes the case for a different type of QE"--
The great experiment -- Understanding money -- QE for the people: a better way -- Some (weak) objections to QE for the people -- Lessons for the next depression.
Machine generated contents note: Introduction Section 1 The Great Experiment Section 2 Understanding Money Section 3 QE for the People: A Better Way Section 4 Some (Weak) Objections to QE for the People Section 5 Lessons for the Next Depression Notes.
Includes bibliographical references.
Keywords: Quantitative easing (Monetary policy); Economic policy